Global warming could hit rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
American scientists are worried that changes in the <<greenhouse effect>> are affecting the earth's climatic pattern and could cause drought and a rise In the ocean level in the next decade. Ultraviolet exposure decreases photosynthesis...